Cuitan Tabu Generasi Y dan Z dalam Komunitas Ngeluh Safe Space di Sosial Media X - Dyah Nur Fadillah; Chattri Sigit Widyastuti (Hasta Wiyata, 2025)
Nowadays, the use of language is considered one of the best ways of communication to demonstrate a pattern of interaction among social media users. One of the most familiar sources of information among Generation Y and Z in Indonesia is tweets on the X social media application. The numerous tweets posted by X social media users have given rise to linguistic phenomena that can be studied, one of which is taboo language. This research will focus on verbal taboos or language taboos that use words or phrases in social interactions on X social media. The research method used is a descriptive qualitative method. The results of the research found the use of language taboos among Generation Y and Z in the Ngeluh Safe Space community on application X, including 9 types of language taboo categories, 3 functions of language taboos, and 4 causes for the use of language taboos.